2016
DOI: 10.1123/jsep.2015-0286
|View full text |Cite
|
Sign up to set email alerts
|

Can You Have Your Vigorous Exercise and Enjoy It Too? Ramping Intensity Down Increases Postexercise, Remembered, and Forecasted Pleasure

Abstract: There is a paucity of methods for improving the affective experience of exercise. We tested a novel method based on discoveries about the relation between exercise intensity and pleasure, and lessons from behavioral economics. We examined the effect of reversing the slope of pleasure during exercise from negative to positive on pleasure and enjoyment, remembered pleasure, and forecasted pleasure. Forty-six adults were randomly assigned to a 15-min bout of recumbent cycling of either increasing intensity (0-120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 19 publications
6
103
1
2
Order By: Relevance
“…We also argue that SIT and HIIT are unlikely to be experienced as pleasant and enjoyable for most people and that such anticipated displeasure and effort will also damage exercise adherence [19]. Finally, we disagree that disciplinary rivalry exists and note that the previous commentary was co-authored by both physiologists and psychologists working together undertaking HIIT research [13].…”
Section: Commentarymentioning
confidence: 82%
“…We also argue that SIT and HIIT are unlikely to be experienced as pleasant and enjoyable for most people and that such anticipated displeasure and effort will also damage exercise adherence [19]. Finally, we disagree that disciplinary rivalry exists and note that the previous commentary was co-authored by both physiologists and psychologists working together undertaking HIIT research [13].…”
Section: Commentarymentioning
confidence: 82%
“…There is concern that HIIT exercise may transiently increase the risk of adverse coronary events but trials that are large enough and long enough to assess the associated risk accurately have not been completed 35. In addition, although HIIT offers a time saving alternative to moderate intensity continuous training, in previously inactive, unfit middle aged and older participants, pleasure seems to decrease as the intensity of exercise increases,36 which may negatively influence long term compliance.…”
Section: Cardiovascular Disease and Cardiac Rehabilitationmentioning
confidence: 99%
“…In this context, it is imperative that patients find pleasure in exercising. Yet, Zenko et al 23 clearly showed that in sedentary and low-fitness participants, pleasure reduces with increasing exercise intensity. In this sense, HIIT might negatively influence compliance and the adoption of a lifelong physically active lifestyle.…”
mentioning
confidence: 99%
“…In this sense, HIIT might negatively influence compliance and the adoption of a lifelong physically active lifestyle. To date, none of the published comparative HIIT and MCT trials interviewed participants about the enjoyment and attractiveness of the training protocols, but the findings from Zenko et al 23 may also hold true for cardiac patients.…”
mentioning
confidence: 99%